Beyond Boundaries: Negotiations of National Identity in Den Vlaemschen Indicateur (1779–87) and the Journal des Pays-Bas autrichiens (1786) - Van Puyvelde, Vanessa (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
As the Brabant Revolution of 1789 came ever closer, the idea of national unity slowly took hold in the Southern Netherlands, that is, present-day Belgium. The current study looks at how this national consciousness arose in the years preceding the Brabant Revolution. Through an analysis of two literary journals, Den Vlaemschen Indicateur (1779–87) and the Journal des Pays-Bas autrichiens (1786), this essay identifies and examines how national belonging was imagined and articulated through fiction, either through poems, anecdotes, or imaginary letters. Taken together, these case studies illustrate the importance of literary journals in the Southern Netherlands as they fostered a period of nation-building, which was cultural rather than political. By reconstructing the social and biographical trajectories of the editors of these journals, this study brings clarity to the history of proto-Belgian journalism as it emerged during the second half of the eighteenth century.